Determinants of Sexual Practices Among Secondary School Students in Nigeria: Focusing on Socio-Cultural and School-Related Factors - K. Kanmodi; O. Fagbule; K. Ogunniyi; M. Ogbeide; V. Samuel; E. Aliemeke; Y. Olatunji; T. Isola; H. Adewuyi; S. Musa (Rwanda Medical Journal, 2020)
BACKGROUND: Very little is known about the school-related and sociocultural determinants of sexual practices amongst Nigerian secondary school students. This study aims to determine such factors amongst them. METHODS: This was a descriptive questionnaire-based cross-sectional survey of 2,530 students from 13 Nigerian secondary schools. RESULTS: Roughly a fifth (22.1%) of the respondents had engaged in sex and their mean (±SD) age of sexual debut was 13.8 (±3.6) years; 82.3% and 53.6% of those who had ever had sex had a history of vaginal sex and oral sex, respectively. Also, 52.3% and 58.9% of those with a history of vaginal sex and oral sex had multiple sexual partners, respectively. No significant difference exists between respondents’ lifetime sexual history and school type (private versus [vs.] public); student’s class (SS 1 vs. SS2 vs. SS3); and mode of the studentship (day vs. boarding) (p-values>0.05). However, the following factors were found to predict a positive history of engagement in sexual practices amongst the respondents: age ≥ 20 years (aOR:5.24; 95%CI:2.21-12.46); age 15-19 years (aOR:1.99; 95%CI:1.02-3.88); studying in northern Nigeria (aOR:1.96; 95%CI:1.02-3.88); being a Yoruba (aOR:2.28; 95%CI:1.24-4.22); being male (aOR:1.89; 95%CI:1.17-3.04); and being a Muslim (aOR:2.17; 95%CI:1.30-3.64). CONCLUSION: Age, gender, school location, tribe, and religion were significantly associated with the positive sexual history of Nigerian secondary school students.